THE CORRELATION OF THE INTENSITY OF LIGHTING THE WORK ROOM MYOPIA’S INCIDENCE OF WORKER LASHES IN EYELASH PLASMA IN DISTRIC OF KEJOBONG REGENCY OF PURBALINGGA - Tri Anasari; Endang Sri Rahayu; Ulfa Fadila Rudatiningtyas; Yuli Trisnawati (Kesmas Indonesia, 2023)
False eyelashes are a highly developed home industry in Purbalingga Regency. One part of the core eyelash work is kneeting which requires eye concentration. Working relatively close, with lighting that does not meet standards will have an impact on eye damage. Refractive errors in Purbalingga Regency in 2021 ranked first, namely 463 cases of myopia, 184 cases of hypertrophy, 58 cases of presbyopia, and 97 cases of astigmatism. The aim of the study was to determine the relationship between lighting intensity in the workspace and the incidence of myopia in eyelash workers in the plasma area of Kejobong Purbalingga District. The research method is an analytic survey with a cross-sectional design. Sampling by purposive sampling. The number of samples is 55 respondents. Primary data was taken by making observations, namely measuring myopia with the Snellen card and measuring light intensity with a lux meter. Univariate data analysis used the frequency distribution test, bivariate analysis used the chi-square test. The distribution of respondents was dominated by lighting intensity that did not meet standards (65.5%) and those with myopia (67.3%). The results of the bivariate analysis showed that there was a relationship between the intensity of lighting in the workspace and the incidence of myopia (p-value = 0.00 <0.05). Eyelash workers who work in a room where the lighting intensity does not meet the standard have an 8.5xgreater chance of experiencing myopia than those with a lighting intensity that meets the standard.